2020
DOI: 10.1155/2020/8877161
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Technology of Tennis Sports Match Based on Data Mining and Image Feature Retrieval

Abstract: Tennis game technical analysis is affected by factors such as complex background and on-site noise, which will lead to certain deviations in the results, and it is difficult to obtain scientific and effective tennis technical training strategies through a few game videos. In order to improve the performance of tennis game technical analysis, based on machine learning algorithms, this paper combines image analysis to identify athletes’ movement characteristics and image feature recognition processing with image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…For the method in OATPP [6], the minimum recognition accuracy is 75%, and DMMSD [7] is 73%, while ODMM [8] method is 71%. The recognition accuracy of the proposed method is 17% higher than that the method in ATTS [4], 13% higher than DMPL [5], 22% higher than OATPP [6], 24% higher than DMMSD [7], and 26% higher than ODMM [8]. These results demonstrate that the defensive posture recognition accuracy of the proposed method is higher, indicating favorable practical application outcomes.…”
Section: Resultsmentioning
confidence: 74%
See 3 more Smart Citations
“…For the method in OATPP [6], the minimum recognition accuracy is 75%, and DMMSD [7] is 73%, while ODMM [8] method is 71%. The recognition accuracy of the proposed method is 17% higher than that the method in ATTS [4], 13% higher than DMPL [5], 22% higher than OATPP [6], 24% higher than DMMSD [7], and 26% higher than ODMM [8]. These results demonstrate that the defensive posture recognition accuracy of the proposed method is higher, indicating favorable practical application outcomes.…”
Section: Resultsmentioning
confidence: 74%
“…The minimum recognition accuracy of the proposed method is 97%. The method in ATTS [4] has a minimum recognition accuracy of 80%, while the method in DMPL [5] achieved a minimum recognition accuracy of 84%. For the method in OATPP [6], the minimum recognition accuracy is 75%, and DMMSD [7] is 73%, while ODMM [8] method is 71%.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is often difficult to obtain scientific and effective tennis technical training strategies through some game videos. To improve the performance of technical analysis of tennis competition, Huang and Deng (2020) [11] combined image analysis with image recognition technology based on ML algorithm and used image recognition technology to extract the motion features of athletes to track their dynamic features and record their technical features in real-time. Yang and Zhang (2021) [12] revealed that the tennis research force, as one of the main driving forces to promote the development of tennis in China, was an important means to guide the scientific development of tennis to understand the development characteristics and research trend of tennis teaching mode in China and could provide the theoretical basis for follow-up research and practice.…”
Section: Literature Overviewmentioning
confidence: 99%